2015
DOI: 10.4314/mejs.v7i2.8
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Mortality and Exploitation Rates of <i>Sarotherodon melanotheron</i> in the Dominli Lagoon of Ghana

Abstract: Sarotherodon melanotheron population of Dominli Lagoon in the Western Region of Ghana was studied for its growth and mortality parameters as well as exploitation rate. The study generally aimed at providing basic information necessary for the assessment and management of the fish stock in the lagoon. Using FiSAT programme, estimates of the prominent growth and mortality parameters of S. melanotheron were: L ∞ = 20.48 cm, SL and K = 0.97yr -1 . Total, natural and fishing mortalities of the population were deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 15 publications
2
3
1
Order By: Relevance
“…Arizi et al. (2014) reported a sex ratio of 1:1.5 which is similar to the finding of the current study. Deviation from the normal 1:1 sex ratio periodically or permanently can occur during spawning, temperature variation, distribution of organisms in time and space and the availability of food (Famoofo & Abdul, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Arizi et al. (2014) reported a sex ratio of 1:1.5 which is similar to the finding of the current study. Deviation from the normal 1:1 sex ratio periodically or permanently can occur during spawning, temperature variation, distribution of organisms in time and space and the availability of food (Famoofo & Abdul, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…This implies that fishes from the Brimsu reservoir will reach their asymptotic length faster than fishes from Nyanza Gulf (Kenya), Siyambalangamuwa, Balaluwewa and Ibbankatuwa reservoirs in Sri Lanka. The L ∞ value for S. melanotheron was high, even though the K and M values were smaller than those reported in the Dominli and Etsir Lagoons (Arizi et al, 2015;Tibu et al, 2019). Maximum length reached by a fish is a crucial factor highly correlated with metabolism and other life-history traits (Binohlan & Froese, 2009).…”
Section: Growth and Reproduction Parameters Of The Two Cichlidsmentioning
confidence: 58%
See 2 more Smart Citations
“…Divakar et al (2017) found that the maximum recruitment percentage was observed in August (31.00%) for Katsuwonus pelamis, where the period remained between July and October. The annual recruitment pattern of Sarotherodon melanotheron found in the rainy season (April -July) and dry season (October -January) had maximum and minimum recruitment in June and February (Arizi et al 2015), which is close to the present findings.…”
Section: Patterns Of Recruitmentsupporting
confidence: 91%